The Effect of the Problem Based Learning Model on Students’ Communication Skills and Learning Outcomes in Ecosystem Material - Ayu Andira Hasibuan; Marlinda Nilan Sari Rangkuti (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to determine the effect of the problem-based learning model on students' communication skills and cognitive learning outcomes regarding the topic of ecosystems at SMA Negeri 1 Kualuh Leidong. A quasi-experimental design specifically a pretest-posttest non-equivalent control group design was employed, involving 72 students from two classes selected via random sampling. The experimental class utilized the problem-based learning model, while the control class underwent conventional instruction. Communication skills were measured using observation sheets, and cognitive learning outcomes were assessed through multiple-choice tests. The results indicate that the experimental class achieved an average communication skill score of 87.67% (categorized as highly skilled), which was significantly higher than the control class's score of 55.44% (categorized as skilled). Cognitive learning outcomes also showed significant improvement; the experimental class achieved an N-gain score of 0.75 (high category), compared to 0.47 (medium category) for the control class. Mann-Whitney U test results indicate that the problem-based learning model significantly influences communication skills, while Independent Sample t-test results show that problem-based learning significantly affects biology learning outcomes regarding the topic of ecosystems. This study demonstrates that problem-based learning is an effective instructional model for developing students' communication skills and enhancing their biology learning outcomes, particularly concerning the ecosystem topic.